Review of skeletal carbonate mineralogy of brachiopods with new material from New Zealand - Abigail M. Smith; David F. Freeman; Ian S. Dixon‐Anderson; Daphne E. Lee (New Zealand Journal of Marine and Freshwater Research, 2024)
We combine published and new mineralogical data on most major taxa of brachiopods from all over the world, to investigate patterns and controls on brachiopod carbonate mineralogy. Measurements of 1726 specimens in 162 species (including 56 fossil species) ranged from 79°N to 74°S and from intertidal to almost 4000 m deep. Calcareous brachiopods mostly create strong resilient valves of very low‐Mg calcite ( = 1.3 wt% MgCO 3 ). The substrate‐cemented Craniida ( = 8.9 wt% MgCO 3 ) and Thecideida ( = 6.5 wt% MgCO 3 ) are unusual in precipitating calcite with higher Mg content. This is the first study to find bimineralic brachiopods; a few species show a combination of low‐Mg ( = 0.8 wt% MgCO 3 ) and intermediate‐Mg calcite ( = 7.2 wt% MgCO 3 ) ( sensu Smith AM, Key MM Jr, Gordon DP. 2006. Skeletal mineralogy of bryozoans: taxonomic and temporal patterns. Earth‐Science Reviews. 78:287–306.). While Mg in calcite varies systematically among valve layers and sometimes along the growth axis, we found no consistent difference between valves of the same individual. A weak latitudinal signal indicates some overall temperature control of Mg, but in general, brachiopods are active calcifiers, precipitating low‐Mg calcite even when Mg:Ca ratio in seawater is high. The drivers on brachiopod mineralogy are individual, environmental, and phylogenetic – resulting in complex variability.